An initial palaeosalinity history of Jaw Lake, Bunger Hills based on a diatom-salinity transfer function applied to sediment cores - Roberts, D; Andrew McMinn; Zwartz, D (2000)
Two sediment cores taken from Jaw lake (Bunger Hills, East Antarctica) were analysed for diatom composition and abundance. A diatom-salinity transfer function developed for the nearby Vestfold Hills was used to determine palaeosalinity reconstructions from the assemblages preserved in each of the cores. There is a large step-wise decrease in salinity in the second core from at least c. 4000 to c. 2000 uncorrected 14C yr BP. The salinity record from the first core starts at c. 3000 uncorrected 14C yr BP and is comparable with the salinity of the second core between c. 3000 and c. 2000 uncorrected 14C yr BP. Sudden lake water dilution in both cores at c. 1900 uncorrected 14C yr BP is followed by brief increases in lake water salinity between c. 1900 and c. 500 uncorrected 14C yr BP, after which gradual dilution to present occurs. This analysis of the local environmental history of this saline lake reveals a mid-late Holocene evolution of the lake basin similar to that documented from earlier marine and freshwater lacustrine sediments in the Bunger Hills. The high coherence of the independent sediment records suggests a robust general palaeosalinity reconstruction of the lake is achieved in addition to providing evidence for the fidelity of single sediment cores as useful and adequate representation of the palaeolimnological histories of Antarctic lakes.